Tailoring superhydrophobic ZnO nanorods on Si pyramids with enhanced visible range antireflection property. (10th July 2019) - Sharma, D; Bhowmick, S; Das, A; Kanjilal, A; Saini, C P
Abstract: Simultaneous superhydrophobic and visible range antireflective properties are demonstrated in hydrothermally grown ZnO nanorods (NRs) on chemically textured Si surfaces. A drastic transformation of Si micro-pyramids from hydrophobic to superhydrophobic is observed by securing the formation of polycrystalline ZnO NRs at surfaces, showing an increment of apparent contact angle from ∼102° to ∼157° and further explained in the light of a decrease in solid fractional surface area, according to the Cassie-Baxter model. Moreover, wurtzite phase of ZnO NRs is confirmed by the x-ray diffraction and Raman analysis. Such hierarchical structures further exhibit a large visible range antireflection (∼5%), and correlated it to the variation in aspect ratio of Si pyramids in conjunction with the formation of graded refractive index. The combined superhydrophobic and large antireflection phenomena in the present dual-scale structures is believed to be useful for Si-based photovoltaic applications.